EFEKTIVITAS PELATIHAN PENGENDALIAN DIRI UNTUK MENGATASI PERILAKU BULLYING SISWA DI SMP NEGERI 19 AMBON - Jeanete Ophilia Papilaya; Nessy Pattimukay (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2017)
This study purpose to a) assess the effectiveness of self-control training to address bullying behavior of students, b) Conduct training self-control to overcome the bullying behavior of students. To achieve that goal then used experimental research design with the one- group pretest-posttest design. hypotheses used are effective self-control training to resolve bullying behavior of students. Data obtained from 24 students who demonstrate bullying behavior. Analysis using t- test with SPSS version 16.0 of the calculation of the results found t> t table (7232> 1714). From the results of t-test analysis found that effective self-control training to address bullying behavior of students.